Towards a Common Vision for Climate Security in Senegal (workshop report) - Medina, Leonardo; Sarzana, Carolina; Jaquet, Stéphanie; Villa, Victor; Läderach, Peter R.D.; Pacillo, Grazia (2022)
This memory report presents the main findings of the ClimBeR climate security workshop held in Senegal in October 2022. This workshop brought together over 35 stakeholders from Senegal's humanitarian, development, climate and peace sectors, including government representatives, NGOs, international organizations, and research institutes, with the goal of appraising climate and insecurity linkages in Senegal and targeting programmatic, evidence-based and policy-related solutions to address them.